Herbicide based weed management for semi dry rice (Oryza sativa L.) - Arya S R (Department of agronomy, College of agriculture, 2015)
An investigation entitled “Herbicide based weed management for semi dry rice (Oryza sativa L.)” was conducted during the period May to September 2014 at farmer’s field in Nemom block, Thiruvanthapuram. The main objectives of the study were to evaluate the weed control efficiency of new generation herbicides in semi dry rice, to assess their selectivity and influence on growth and yield, to work out the economics and to develop a weed management strategy for semi dry rice. The field experiment comprised of eleven treatments replicated thrice (Variety: Uma) was laid out in randomised block design. The treatments were T1: bensulfuronmethyl + pretilachlor @ 60 + 600 g a.i. ha-1 (pre - emergence), T2: T1 + hand weeding at 40 DAS, T3: T1 + azimsulfuron @ 30 g a.i. ha-1 (post emergence), T4: pyrazosulfuron ethyl @ 25 g a.i. ha-1 (pre - emergence), T5: T4 + hand weeding at 40 DAS, T6 : T4 + azimsulfuron @ 30 g a.i. ha-1 (post emergence), T7 : oxyfluorfen @ 0.15 kg a.i. ha-1 (pre - emergence), T8 : T7 + hand weeding at 40 DAS, T9 : T7 + azimsulfuron @ 30 g a.i. ha-1 (post emergence) and two controls: T10: hand weeding at 20 and 40 DAS and T11: weedy check. Result of the study revealed substantial reduction in weed population and biomass in all the herbicide treated plots compared to weedy check. Weed composition of the experimental field indicated the dominance of broad leaved weeds followed by sedges and grasses with considerable variation in weed flora during dry and flooded condition. Hand weeding at 20 and 40 DAS (T10) recorded lowest weed density, weed dry weight and highest weed control efficiency. Absolute frequency (Af) for all weed species throughout the crop growth stages was also lower under hand weeding while higher values of importance value (IV) and summed dominance ratio (SDR) for sedges and broad leaved weeds were recorded in weedy check (T11). Pre-emergent herbicide application followed by either hand weeding at 40 DAS (T2 and T5) or application of post emergent herbicides (T3 and T6) recorded higher weed control efficiency and lower nutrient removal in comparison with hand weeding twice (20 and 40 DAS). None of the herbicides produced any phytotoxic symptoms on rice plant. However, crop density and growth was lower at the initial stages in oxyfluorfen treated plots. This indicated that bensulfuron methyl + pretilachlor and pyrazosulfuron can be treated as safe pre-emergent herbicides for dry sown (semi dry) system of rice cultivation. Result of the study also indicated the safety of the herbicides on microbial activity as evidenced by the increase in soil dehydrogenase activity in herbicides applied plots. The yield attributes of rice viz., number of productive tillers m-2 and filled grains panicle-1 were significantly influenced by the weed management practices T2, T3, T5, T6 and T10. Grain yield (4817.67 kg ha-1) and straw yield (7969.33 kg ha-1) were significantly higher in T2 (bensulfuronmethyl + pretilachlor @ 60 + 600 g a.i. ha-1 + hand weeding at 40 DAS) and remained on par with T3, T5, T6 and T10. Yield loss due to weeds was found to be 52.22 per cent. The most economically viable weed management practice was T6 (bensulfuronmethyl + pretilachlor fb azimsulfuron) with a B: C ratio of 1.76 which was on par with T3 (1.75). Grain yield, net income and B: C ratio were significantly lower in weedy check. It can be concluded that the most effective weed management practice for semi dry rice is pre-emergence application of either bensulfuron methyl + pretilachlor @ 60 + 600 g a.i. ha-1 or pyrazosulfuron ethyl @ 25 g a.i. ha-1 on the next day of sowing followed by post emergence application of azimsulfuron @ 30 g a.i. ha-1 at 25 DAS.